Honduras: The impact of COVID-19 and implications: Second report - Díaz-Bonilla, Eugenio; Flores, Luis; Paz, Florencia; Piñeiro, Valeria; Zandstra, Tamsin (International Food Policy Research Institute, 2021)
Due to the global pandemic generated by COVID-19 the government of Honduras declared a “state of emergency” in February (“Estado de Emergencia en el Territorio Nacional a través del Decreto Ejecu-tivo Número PCM- 005-2020, 10 de febrero 2020). The country suffered the first confirmed COVID-19 case on March 12th, 2020. The first death was registered on March 26, 2020. This document updates a previous report (Díaz Bonilla, Laborde, and Piñeiro, 2021) on the impact of the COVID-19 pandemic on food systems in Honduras. First, it brings up to date the evolution of the pandemic, using different indicators. Second, it summarizes the main responses, costs, and fi-nancing. Third, it updates the evolution of key variables up to the time of this writing (June 2021). Fourth, there is a more detailed analysis of the evolution of some food value chains that are central for food consumption in Honduras. Fifth, main results for 2021 and 2022 of previous modeling work are briefly presented. A final section discusses considerations in light of the updated analysis.